Making new Nepal : from student activism to mainstream politics - Snellinger, Amanda Thérèse (Global South Asia., 2018)
"This ethnography explores Nepal's political transition in the twenty-first century through the most recent generation of student activists to have entered national politics. Based on multi-sited ethnographic research between 2003 and 2015, it illuminates a generation's political coming of age during a decade of civil war (1996-2006) and ongoing democratic street protests (2003-2006), which finally ousted the monarchy in 2008 and established a democratic secular republic. It tracks this generation's entrée into politics through the stories of five young street activists as they shift to working within mainstream politics. The concept of political regeneration is used to demonstrate how Nepal's history of activism has shaped its political discourse and practice, and how the country's democratic struggle has always been a process in which each new generation establishes itself politically by negotiating between previous acts of claim-making and new political formulations. This case study demonstrates how democracy works as a radical ongoing process rather than a formal sphere, and how the relationship between change and the status quo in Nepali national politics has created youth as a social category in politics."--Provided by publisher.